Management of hypocalcemia following thyroid surgery in children - Romera, Andrea; Barragán, Lourdes; Álvarez-Baena, Lucía; Sanjuán, Erika; Ordóñez, Javier; García-Casillas, María Antonia; Mora, Marina; Sanz, María (Frontiers in Pediatrics, 2023)
Pediatric post-thyroidectomy hypocalcemia management varies significantly from hospital to hospital. The current study has two aims: first, we evaluate demographic data in all pediatric patients submitted to thyroid surgery in our Spanish tertiary hospital over 20 years; secondly, we describe the way that hypocalcemia was diagnosed and treated in that period and present a multidisciplinary protocol for perioperative management of this condition. Methods: This is a retrospective and observational study of all patients from 0 to 16 years old who underwent thyroid surgery from 2000 to 2020 at our institution. Demographic, surgical and electrolyte data were recorded from the electronic database. Results: From 2000 to 2016, pediatric thyroid surgery at our institution was performed on 33 patients without a consistent approach or standard electrolyte management. A protocol for perioperative management of these patients was introduced in 2017, and applied to 13 patients. In 2019, the protocol was assessed and updated following a case of symptomatic hypocalcemia. From 2000 to 2016, 47 pediatric patients in all underwent thyroid surgery. We registered 8 asymptomatic hypocalcemias. One child developed symptomatic hypocalcemia. Two patients have permanent hypoparathyroidism. Discussion: Our incidence of general complications following thyroidectomy was low; hypocalcemia was the most prevalent. Most of these complications occurred when there was no standard approach to electrolyte management. All the cases of hypocalcemia submitted to the protocol were identified early by iPTH measurements. Intraoperative iPTH results could help stratify patients according to their risk of hypocalcemia. High risk patients require immediate postoperative supplementation including calcitriol and calcium carbonate.